Research on the temperature influence and compensation technique in a magneto–elastic cable tension sensor. (27th January 2015) - Tang, Dedong; Zhu, Hongjun; Mou, Julan; Wu, Mingfang
The magneto–elastic cable tension sensor has numerous advantages. For example, it is the ideal method for measuring the cable tension in a large span cable–bridge; however, the sensor is also temperature–sensitive, and as such, the temperature influence on the sensor is a significant factor. In this paper, the principle of cable tension sensor based on magnetic–elastic effect is introduced. And, the theory of temperature influence magneto–elastic material is thoroughly analysed. On the basis of Jiles–Atherton model, which introduced the Curie temperature as an additional parameter, a magnetic–thermo coupling model for the magnet elastic cable tension sensor is constructed. By analysing temperature and the physical parameters of the model, a novel method of compensating for the temperature by adjusting the bias magnetic field is proposed. Theoretical analysis experimental work indicate that the model is a practical means of compensating for temperature influence.